An analytic approach to predict the shape and internal forces of barrel vault elastic gridshells during lifting construction. (February 2021) - Xiang, Sheng; Cheng, Bin; Kookalani, Soheila; Zhao, Jian
Abstract: The barrel vault elastic gridshell is a type of spatial structure composed of long continuous solid timber or hollow GFRP members and achieves its shape from elastic deformations during the construction process of lifting or pushing. The shape forming mechanism of elastic gridshells is very complicated due to significant geometric non-linearity. This research aims to propose analytic formulations to estimate the deformed shapes of barrel vault elastic gridshells considering the mechanical properties of structure. Simplified model of a single member subjected to distributed loads and concentrated forces was established for theoretical analysis, from which the deformations and bending moments of the structure were calculated. Finite element models were further established to validate the accuracy of the proposed approach, and both simple cantilever beams and spatial barrel vault elastic gridshells were employed as investigation objects. Various cases of dimensional parameters were covered so that the wide applicability of such analytical method can be verified. Results show that the derived performance indexes of all members are very close to the results from finite element analysis, indicating that the proposed theoretical approach is effective and efficient in predicting the structural behaviors of barrel vault elastic gridshells when lifting construction method is adopted.